NUMERICAL ANALYSIS BEHAVIOR OF LONG LINK WITH DIAGONAL STIFFENERS ON ECCENTRICALLY BRACED FRAMES - (NIM : 25008007); Pembimbing : Prof. Ir. R. Bambang Budiono, ME., Ph.D, NIDIASARI
Eccentrically Braced Frames (EBFs) are seismic resistant building that demonstrate high stiffness combined with excellent ductility and energy dissipation capacity in inelastic condition. Link is a critical element that dissipated seismic energy within inelastic behavior of EBF. Inelastic behavior of link effected by it’s length. Strength, stiffness, ductility and energy dissipation are decreasing with increasing the link’s length. The aim of this study is to evaluate long link behavior by placing diagonal stiffener in the link. Analysis is conducted using finite element method of MSC/NASTRAN software. Seven links with diagonal stiffener were analysed and compared with link without web stiffener based on recommendation of AISC 2005. In addition link with intermediate stiffener also analysed to verify the result. Results indicated that link with diagonal stiffener is capable to increase maximum load capacity 1.21 larger, stiffness up to 1.21 higher per cycles and energy dissipation 1.12 times compared with link without stiffener. However, diagonal stiffener does not effect the ductility. Besides, link with intermediate stiffener not significantly influenced the link behavior.